Development of a qPCR Method to Measure Mitochondrial and Genomic DNA Damage with Application to Chemotherapy-Induced DNA Damage and Cryopreserved Cells - Evans, Stephen O. (Biology (Basel), 2016)
DNA damage quantitation assays such as the comet assay have focused on the measurement of total nuclear damage per cell. The adoption of PCR-based techniques to quantify DNA damage has enabled sequence- and organelle-specific assessment of DNA lesions. Here we report on an adaptation of a qPCR technique to assess DNA damage in nuclear and mitochondrial targets relative to control. Novel aspects of this assay include application of the assay to the Rotor-Gene platform with optimized DNA polymerase/fluorophore/primer set combination in a touchdown PCR protocol. Assay validation was performed using ultraviolet C radiation in A549 and THP1 cancer cell lines. A comparison was made to the comet assay applied to peripheral blood mononuclear cells, and an estimation of the effects of cryopreservation on ultraviolet C-induced DNA damage was carried out. Finally, dose responses for DNA damage were measured in peripheral blood mononuclear cells following exposure to the cytotoxic agents bleomycin and cisplatin. We show reproducible experimental outputs across the tested conditions and concordance with published findings with respect to mitochondrial and nuclear genotoxic susceptibilities. The application of this DNA damage assay to a wide range of clinical and laboratory-derived samples is both feasible and resource-efficient.